Edge Computing and 5G: Catalyzing the Next Generation of IoT Innovation - Kiran Kumar Sunkara (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the transformative convergence of edge computing and 5G networks in revolutionizing the Internet of Things (IoT) landscape. The article examines how these complementary technologies address critical challenges in modern distributed systems, focusing on performance optimization, network efficiency, and security enhancement. Through comprehensive analysis of implementation cases across healthcare, industrial automation, and agriculture sectors, the article demonstrates significant improvements in latency reduction, resource utilization, and operational efficiency. The article encompasses the evolution of edge computing architectures, the revolutionary capabilities of 5G networks, and their combined impact on enabling next-generation IoT applications. The article also evaluates future implications and emerging opportunities in algorithm development, security frameworks, and scalable architecture design.